Effect of polycystic ovary syndrome on cardiac autonomic function at a late fertile age: a prospective Northern Finland Birth Cohort 1966 study. Issue 12 (15th December 2019) - Ollila, Meri-Maija; Kiviniemi, Antti; Stener-Victorin, Elisabet; Tulppo, Mikko; Puukka, Katri; Tapanainen, Juha; Franks, Stephen; Morin-Papunen, Laure; Piltonen, Terhi
Abstract : Objectives: Previous studies of women in their 20s and 30s have reported impaired autonomic function in women with polycystic ovary syndrome (PCOS). We aimed to study, for the first time, whether PCOS is associated with impaired cardiac autonomic function independent of metabolic and hormonal status in their late reproductive years. Design: A prospective Northern Finland Birth Cohort 1966 (NFBC1966) study including 5889 women born in 1966 and followed through the age of 46. At that age, n=3706/5123 women (72%) answered the postal questionnaires and n=3280/5123 women (64%) participated in the clinical examination. Setting: General community. Participants: The sample included women presenting both irregular menses (oligomenorrhoea or amenorrhoea) and hirsutism at age 31 (n=125) or with formally diagnosed PCOS by age 46 (n=181) and women without PCOS symptoms or diagnosis (n=1577). Primary and secondary outcome measures: Heart rate variability parameters: the root mean square of successive R-R differences (rMSSD), spectral power densities (LF: low frequency and HF: high frequency) and baroreflex sensitivity (BRS). Results: We found that parasympathetic activity (assessed by rMSSD: 19.5 (12.4; 31.9) vs 24.3 (16.1; 34.8) ms, p=0.004 and HF: 172 (75; 399) vs 261 (112; 565) ms 2, p=0.002) and BRS (6.13±3.12 vs 6.99±3.52 ms/mm Hg, p=0.036) were lower in women with PCOS compared with the controls. However, in the multivariate regression analysis, PCOS, body mass index and the free androgen index did not significantly associate with rMSSD, whereas blood pressure, insulin resistance and triglycerides did. Conclusions: We report here for the first time that late reproductive-aged women with PCOS display impaired cardiac autonomic function manifested as decreased vagal activity. Metabolic status, rather than hyperandrogenaemia and PCOS per se, was the strongest contributing factor. Given the link between cardiac morbidity and impaired autonomic function, the findings underline the importance of screening and treating metabolic abnormalities early on in women with PCOS.